2009
DOI: 10.1016/j.nbt.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric hepatitis B and C viruses envelope proteins can form subviral particles: implications for the design of new vaccine strategies

Abstract: The hepatitis B virus (HBV) envelope protein (S) self-assembles into subviral particles used as commercial vaccines against hepatitis B. These particles are excellent carriers for foreign epitopes, which can be inserted into the external hydrophilic loop or at the N- or C-terminal end of the HBV S protein. We show here that the N-terminal transmembrane domain (TMD) of HBV S can be replaced by the TMDs of the hepatitis C virus (HCV) envelope proteins E1 and E2, to generate fusion proteins containing the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…Similar results have been reported recently for HBsAg chimeras containing the ectodomains and TM domains of envelope proteins E1 and E2 of hepatitis C virus (11,33). These authors replaced TM1 of HBsAg with the TM domains of the HCV envelope proteins E1 and E2.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results have been reported recently for HBsAg chimeras containing the ectodomains and TM domains of envelope proteins E1 and E2 of hepatitis C virus (11,33). These authors replaced TM1 of HBsAg with the TM domains of the HCV envelope proteins E1 and E2.…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies, based on the deletion of membrane-spanning domains, showed that transmembrane domains TM1 and TM2 were required for particle formation (5,6). However, subsequent studies have shown that, at least for TM1, the replacement of amino acids is permitted (21,33). In this paper, we have substituted an entire TM domain of another transmembrane protein (HIV gp41) for TM1 or TM3 of HBsAg and probed the requirements for particle assembly.…”
mentioning
confidence: 99%
“…However, mutagenesis of three hydrophobic clusters of amino acids in TM1 demonstrated that these residues were critical for S protein expression as well as for infectivity in the background of the L protein (17). On the other hand, a chimera consisting of an N-terminal hepatitis C virus E1 domain, including its transmembrane region, fused to the portion of the HBV S protein downstream of TM1 also was able to be cosecreted with wild-type S protein as SVP (18). In this construct the hepatitis C virus-derived TM replaced TM1.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its N-terminal ectodomain tolerates large heterologous insertions derived from, for example, HIV, globin, or green fluorescent protein [85,102,103]. While former studies demonstrated an essential role of the TM segments in SVP biogenesis [85,86], two recent reports showed that TM1 and TM3 of S could be replaced by foreign TM domains derived from human immunodeficiency virus (HIV) and hepatitis C virus envelope proteins [102,104]. Hence, SVP formation appears to depend on a functional TM domain rather than on S-specific TM sequences.…”
Section: Assembly and Release Of Empty Envelope Particlesmentioning
confidence: 99%